POLA KEPEKAAN ANTIBIOTIK ORAL PADA INFEKSI SALURAN KEMIH KOMUNITAS PADA PASIEN PEDIATRIK RS X TAHUN 2022 - Layanto, Nicolas; Dharmawan, Ade; Gunardi, Wani Devita; Rina, Veronica (Universitas Udayana, 2024)
Some pediatric urinary tract infection show unspesific symptoms and can be treated as an outpatient. Right oral antibiotic can prevent those infection become more severe. All urin sample from pediatic patient without history of antibiotic before sample were taken were collected for one year to get antibiotic pattern from oral antibiotic such as amoxicillin, amoxicillin clavulanat, cefixime, cotrimoxazole, and fosfomycin from all pathogen. All pediatric patient were classified by age. From 0-1 year group dan 1-3 years old group, Proteus mirabilis, Eschericia coli and Enterococcus sp. are the most common bacteria found while oral antibiotic with highest sentivity are cotrimoxazole and fosfomycin. Most Multi Drug Resistant bacteria found in this study were from 0-1 year old group